Investigating the Maritime Freight-Induced EKC Hypothesis: The Case of Scandinavian Countries - YAZICI, Sabire (Frontiers in Environmental Science, 2022)
Countries are concerned about the environmental dirtiness problems due to CO2 emissions. Majority of the countries try to fix this issue by developing several policies. The major goal of this paper is to reveal the coefficient of influence factors on carbon emissions by considering different time periods within the framework of implementation of policy makers. In this context, the research paper explores the relationship between economic growth, energy consumption and CO2 emissions within the frame of environmental Kuznets curve hypothesis. However, this manuscript considers the linkage among logistics sector and CO2 emissions in terms of the environmental Kuznets curve hypothesis for Denmark, Sweden, Norway and Finland from 1960 to 2015 which replaced the sea transportation as independent aside from (economic growth) Gross Domestic Product and energy consumption. The Fourier Shin co-integration test, fully modified least square, dynamic least square, canonical co-integrating regression and autoregressive distributed lag bound test models are performed from 1960 to 2015 (as two separate periods) as annual data in order to reveal the long-run relationship between variables within the scope of environmental Kuznets curve hypothesis for Scandinavian countries including Denmark, Sweden, Norway and Finland. According to results of autoregressive distributed lag bound test, if maritime freight increases by 1 %, CO2 emissions increases by 0.2723. A 1 % increase in energy consumption increases CO2 emissions by 0.3356%. Short term autoregressive distributed lag bound test findings ascertain that the major factors of CO2 emissions in the short-term are changed in maritime freight, energy consumption, and Gross Domestic Product at a 1% significance level for Denmark due to the explosive growth of the transportation sector, coupled with a significant rise in greenhouse gas emissions from this sector, preventive policies should be followed. In order to avoid the pollution from transportation, it is essential to carry out its necessary drivers. In addition, policy maker should kick start applications of new technology in transportation to reduce the pollution by releasing new energy saving vehicles. In this sense, transportation carbon tax, and strengthening incentives for energy conservation should be implemented.